La volition, entre motivation et cognition : quelle place dans la pratique des étudiants, quels liens avec la motivation et la cognition? - Mireille Houart; Sylviane Bachy; Sylvie Dony; Delphine Hauzeur; Isabelle Lambert; Chantal Poncin; Pauline Slosse (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper reports the findings of a study by the AdAPTE group as part of its research on the volition of students in higher education. Based on the results of a survey among nearly 2,200 first-year students in 16 institutions of higher education, it focuses on how students manage learning activities, more specifically syntheses, in autonomy.The questionnaire is divided into three parts. Part one defines the profile of participants. Part two addresses students’ perceptions of their motivation, volition profile and cognitive behaviour. Finally, part three examines how students use volitional strategies classified into six categories.The results of this survey revealed various links. As regards motivation, it appears that students who get to work and stay at work feel more competent and enjoy it more than others. At the cognitive level, a link between cognitive engagement and volition profile was identified. The concordance analysis between generic strategies and their implementation through specific strategies made it possible to identify which one should be particularly exercised either with all the students or with a subset of them in the context of academic achievement support.Thanks to these results, teachers and methodological assistants are offered useful hints to make students more active, attentive and persevering at the beginning of higher education.